(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
In order to guarantee medication safety, enhance clinical procedures, and safeguard the public’s health, pharmacovigilance is essential in identifying and controlling adverse drug reactions (ADRs). Expert systems are crucial for quickly detecting safety issues and averting product withdrawals because to the increasing amount of ADR data. Complex, cross-border safety issues can be better managed by implementing independent review methods and fortifying the worldwide pharmacovigilance network, such as through the Uppsala Monitoring Center. The creation of pharmacovigilance centers around the world has strengthened medication safety monitoring, despite ongoing issues including underreporting and data quality. Initiatives since the year 2000 have concentrated on enhancing drug safety systems, encouraging cooperation between researchers, healthcare providers, and regulatory bodies, and extensively sharing safety data. Pharmacovigilance developments have changed the strategy from changing from reactive to proactive, filling in the gaps, and enhancing medication safety. Along with lowering patient harm and promoting sensible prescription usage, these advancements have also increased confidence in healthcare systems around the world. Pharmacovigilance is becoming a vital instrument for public health protection.